THE RELATIONSHIP BETWEEN FAMILY CHARACTERISTICS IN THE IMPLEMENTATION OF BASIC FEEDING RULES IN CHILDREN AGED 24-36 MONTHS IN KEDUNGMUNDU VILLAGE, SEMARANG CITY (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Basic feeding rules are the basic rules for the feeding practice. Basic feeding rules consist of assigning the feeding schedule, the duration of eating, and the conducive environment for eating. However, children from 1-3 years which is the golden age growth period, still face several growth and development problems, one of these factors comes from the family. As the closest party to the children, the family is considered inadequate to play their optimal role as a motivator, facilitator, and educator. This study aims to analyze to analyze there is a relationship between family structure and application basic feeding rules in children aged 24-36 months in Kedungmundu Village. This research used 68 samples of children aged 24-36 months, taken by purposive sampling method. The study was quantitative research with a cross-sectional approach. The instrument used was a family characteristics questionnaire that has been analyzed for its validity and reliability. In this research, bivariate analysis was conducted. The Chi-Square correlation test was used to all independent variables other than age with basic feeding rules were applied. Meanwhile, the T-Test was used to the age of children when basic feeding rules were applied. The results showed 76.5% of respondents applied basic feeding rules and there was a significant relationship between income, parental education, family completeness with basic feeding rules. And there no significant relationship between races, food cultures, children, and child's age with the application of basic feeding rules. There is no significant relationship between certain races, food cultures, children, and child's age with application of basic feeding rules. Instead, applying basic feeding rules, there is a relationship between family income, parental education, and family structure.
Keywords: basic feeding rules; family structure